Медулярний рак щитоподібної залози з місцевими та віддаленими метастазами: тактика лікування та спостереження - Ларін, О. С.; Черенько, С. М.; Нечай, О. П.; Черенько, М. С. (Clinical Endocrinology and Endocrine Surgery, 2011)
Results of surgical treatment and follow up of 93 primary patients with medullary thyroid carcinoma within 1995-2009 years, including 26 (28%) persons with hereditary disease (MEN2 syndrome) were analyzed. The best long term results were observed in group of noninvasive tumor without metastases at the time of operation (39% – clinical and biochemical recovery, 32% – clinical remission). No one patient with extrathyroid tumor invasion or regional/distant metastases has completely recovered. Hereditary forms of disease demonstrated increased aggressiveness in comparison with sporadic carcinomas with higher rate of distant metastases (31% against 21%) and worse survival. Three patients in sporadic group (6%) and four in hereditary group (12%) died from progression of distant metastases within 8-15 years after primary operation. Complete recovery was seen only after radical primary operations. Repeated surgery never led to calcitonine normalization. Implementation of calcitonine screening and genetic testing for Ret-protooncogene mutation is an important task for Ukraine medicine to improve results of medullary carcinoma treatment.